Research Progress on Genome-Scale Metabolic Models of Lactic Acid Bacteria and Their Application in the Food System - LIU Zihao, NI Haojie, LI Wenlu, WANG Fengzhong, WANG Yanbo, ZENG Hong (Shipin Kexue)
Lactic acid bacteria (LAB) play a crucial role in improving the flavor and enhancing the nutritional value food, which have found wide application in the field of food fermentation. Genome-scale metabolic models (GSMMs) serve as essential tools for studying microbial metabolism, which simulate the metabolic networks of microorganisms and accurately describe the genotype-phenotype relationships. Several GSMMs have already been successfully applied to the metabolic regulation of LAB. This article systematically summarizes LAB GSMMs constructed over the past two decades, emphasizing their application in food systems. Moreover, it analyzes the primary challenges and limitations of the GSMMs and gives an outlook on future directions in by combining emerging technologies and innovative ideas. The final goal is to provide valuable insights for the effective and precise application of LAB GSMMs to the intelligent design of microbial communities in the food industry.